The factors affecting bankruptcy phenomenon among youth in Selangor / Norfaezaina Zainodin and Norfarhanna Abd Manap - Zainodin, Norfaezaina; Abd Manap, Norfarhanna (Faculty of Business and Management, 2014)
This paper intends to determine the factors affecting the bankruptcy phenomenon in Selangor. The data ranges from the year 2012 on a yearly basis consist of the independent variables such as debt, lifestyle and financial literacy and bankruptcy cases as dependent variable. The result shows that debts, lifestyle and financial literacy have a significant relationship towards bankruptcy in Selangor. The results suggest that youths in Selangor facing a challenging in managing their financial that may lead to major cases of bankruptcy. This issue needs to be looks more seriously since it already involves youth at early age of 25 years old. An immediate step should be taken in order to protect young people in their formative years from falling into bankruptcy.